Investigation into the impact of storms on sustaining summer primary productivity in the Sub‐Antarctic Ocean. Issue 17 (14th September 2016) - Nicholson, Sarah‐Anne; Lévy, Marina; Llort, Joan; Swart, Sebastiaan; Monteiro, Pedro M. S.
Abstract: In the Sub‐Antarctic Ocean elevated phytoplankton biomass persists through summer at a time when productivity is expected to be low due to iron limitation. Biological iron recycling has been shown to support summer biomass. In addition, we investigate an iron supply mechanism previously unaccounted for in iron budget studies. Using a 1‐D biogeochemical model, we show how storm‐driven mixing provides relief from phytoplankton iron limitation through the entrainment of iron beneath the productive layer. This effect is significant when a mixing transition layer of strong diffusivities ( kz  > 10 −4  m 2  s −1 ) is present beneath the surface‐mixing layer. Such subsurface mixing has been shown to arise from interactions between turbulent ocean dynamics and storm‐driven inertial motions. The addition of intraseasonal mixing yielded increases of up to 60% in summer primary production. These results stress the need to acquire observations of subsurface mixing and to develop the appropriate parameterizations of such phenomena for ocean‐biogeochemical models. Key Points: Storm‐elevated subsurface vertical diffusion accesses the subsurface iron reservoir Intraseasonal entrainment of subsurface iron sustains primary production through summer This requires a transition layer of strong diffusivities beneath the surface mixed layer